Environmental Ethics: Missing Link for Environmental Protection and Restoration - Gupta, Debabrata Das (International Journal of Bio-resource and Stress Management, 2015)
Environmental restoration is the central concern to environmental policy of all organizations/companies. It is also a crucial practical and ethical concern. Ethics as the overall subject of environmental protection and restoration is being gaining paramount importance. Emergence of environmental ethics has been far more enlarged with the canopy of corporate environmental responsibility. This paper, in this background has dealt the issues like (a) ethics and equity, (b) environmental audit and environmental ethics, (c) levels of environmental ethics and (d) range of environmental policy. Three largest issues in international debate at present have direct bearing on ethical issues are (i) the climate change negotiation and the rights of unborn generations, (ii) the biodiversity debate and the value or rights of other species ecosystems and (iii) the earth charter and the value of statements of environmental rights. Author elaborated ethical, legal and social issues (ELSI) of Genome Project and proposed twin strategy to deal with the growing damage to our support systems by ‘DO ECOLOGY’ for developing nations and’ DON’T ECOLOGY’ for industrialized nations. This appears to be a daunting task before us all. We must integrate the best in traditional knowledge and frontier sciences like Biotechnology (BT) and Information and Communication Technology (ICT). What is actually more important is to spread the genetic literacy among the population. We really need science with ethics/ morality, not simply hype. ‘Greed’ cannot be our ‘Need’. We, therefore, need now is proper atmosphere/social ambience for strengthening social understanding on ‘BT’ and putting it in proper place in the overall frame of Science and Technology.